Implementasi Program Wisata Pantai Karangjahe Di Desa Punjulharjo Kecamatan Rembang Kabupaten Rembang - Annafi, Zahra; Megawati, Suci (Universitas Negeri Surabaya, 2024)
Tourism is one of the largest contributors to revenue that can help improve the economy from regional to national. Utilization and development of tourism potential can be used to increase regional economic income. In addition, tourism can create new jobs, drive the creative economy and open up opportunities for local businesses to grow. In 2018, the Rembang Regency Government continued to encourage villages to develop the potential of their tourism villages. Of the existing tourist villages in Rembang Regency, the one with the highest number of visitors is Punjulharjo Village with Karangjahe Beach Tourism as its main attraction. For this reason, this study discusses the implementation of the tourism village program in order to improve the community's economy in Punjulharjo Village, Rembang District, Rembang Regency. The purpose of this research is to describe the implementation of Karangjahe Beach Tourism Program in Punjulharjo Village. This type of research is descriptive with a qualitative approach. The focus of this research is the implementation of Karangjahe Beach Tourism Program in Punjulharjo Village which is reviewed using the theory of policy implementation according to Van Meter and Van Horn. Data collection techniques were conducted through observation, interviews, and documentation. The method used in this research is descriptive method. The results of the research are the implementation of the tourism village program, especially in Karangjahe Beach tourism, has been carried out well, the economic condition of the community has increased. In management, there are still obstacles, namely in the human resources development section and infrastructure facilities that need to be improved. Based on the research results, suggestions that can be given are 1) It is expected to create a culinary tourism area for specialty foods and drinks, 2) It is expected that the manager will increase the number of trash cans and emphasize cleanliness, 3) It is expected to pay more attention to the selfie spot facilities.